Divorcing Upon Retirement: A Regression Discontinuity Study - Elena G. F. Stancanelli (Institute for the Study of Labor (IZA), 2014)
The many facets of retirement have been studied widely by economists. However, the effect of retirement on marriage stability has been ignored in the literature. Retirement represents a dramatic change in individual time allocation that may affect marriage stability. In particular, individuals that grew up in traditional households in which the father did little domestic work and both spouses worked very long hours such as farmer household may find their marriage especially proven by the transition into retirement. We study the effect of retirement on marriage outburst rates using observations on over 200 000 French men and over 166 000 French women aged 50 to 70, drawn from the French Labor Force Surveys over the period 1990 to 2002. Due to reverse causality concerns, we instrument retirement in our divorce model by exploiting legal retirement age in France and applying a regression discontinuity approach. We find a significant increase in divorce rates which soar and almost double upon retirement for individuals of either gender that grew up in a traditional family environment such as a farmer household.
Keywords: J14; C1; C36; 330; ageing; retirement; regression discontinuity